Legal Reform of the Division of Authority for Mining Affairs: Balance between Regional Autonomy and National Interests - Syofyan Hadi; Sultoni Fikri; Baharuddin Riqiey; Islambek Rustambekov (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
This study aims to analyze and find the legal reform of the division of authority for mineral and coal mining affairs between the Central Government and Regional Governments, so that a regulatory model can balance the principle of regional autonomy and national interests. This research is a normative legal research with a statute, conceptual, and case approach. This study found that after Law No. 3 of 2020 and Law No. 6 of 2023, there was a centralization of mineral and coal mining affairs, which led to the creation of injustice and legal uncertainty for autonomous regions. These regulations, from the perspective of balancing the principle of regional autonomy and the principle of national interests, need to be reformed trough the division of mineral and mining affairs between the Central Government and the autonomous regions based on the principle of justice by using the principles of externality, accountability, and efficiency. Meanwhile, the Central Government can use the principle of national strategic interests for several mineral and coal mining sub-affairs. In Addition, the delegation authority model should be removed and Article 18 paragraph (5) of the 1945 Constitution of the Republic of Indonesia needs to be amended, so that the division of government affairs provides justice and legal certainty for autonomous regions.